Lymphocyte generation and population homeostasis throughout life - Yanes, Rolando E. (Semin Hematol, 2016)
Immune aging is a multi-faceted process that manifests as reduced competence to fight infections and malignant cells as well as diminished tissue repair, unprovoked inflammation and increased autoreactivity. The aging adaptive immune system, with its high complexity in functional cell subpopulations and diversity of B and T cell receptors, has to cope with the challenge of maintaining homeostasis while responding to exogenous stimuli and compensating for reduced generative capacity. With thymic involution, naïve T cells begin to function as quasi-stem cells and maintain the compartment through peripheral homeostatic proliferation that shapes the T cell repertoire through peripheral selection and the activation of differentiation pathways. Similarly, reduced generation of early B cell progenitors alters the composition of the peripheral B cell compartment with the emergence of a unique, auto-inflammatory B cell subset, termed age-associated B cells (ABCs). These changes in T and B cell composition and function are core manifestations of immune aging.